Environmental radiation levels in farmlands and associated health impacts in selected areas of Kogi State, Nigeria - John Actor Ocheje; Moses Ejike Onudibia; Ezekiel Andekwe Yangde; Augustina Achimugu (Proceedings of the Nigerian Society of Physical Sciences, 2026)
Monitoring environmental radiation in farming communities is important for safeguarding agricultural production and protecting the people whose livelihoods depend on the land. This study examined ambient gamma radiation levels at 20 farmland sites across four local government areas of Kogi State, Nigeria. Measurements were made with a portable radiation survey meter, while a Global Positioning System (GPS) device was used to record the coordinates of each sampling point. Ambient radiation levels were recorded at each site, and average dose rates were subsequently calculated. The results revealed a mean annual radiation level of 1.4833 mSv y-1, with values ranging from 0.8766$ to 2.279 mSv y-1; the highest value was reported in Ajaokuta. The mean values of the absorbed dose rate (ADR), annual effective dose rate (AEDR), radium equivalent activity (Raeq), external hazard index (Hext), internal hazard index (Hint), and excess lifetime cancer risk (ELTCR) were 79.4447 pm 12.87, 0.0975 pm 0.02, 174.7444 pm 30.89, 0.4720 pm 0.08, 0.6147 pm 0.10, and 0.3412 pm 0.06, respectively. Comparison with international radiation-protection benchmarks suggests that farmers and rural dwellers in the study areas are not currently exposed to levels that pose an immediate health threat. Nevertheless, a few isolated hotspots recorded elevated readings and should be monitored to guard against possible long-term effects. Overall, this work highlights the importance of sustained environmental monitoring and provides baseline radiometric data for agricultural zones in Kogi State.